Reducing CO2 Flow Using Foams. (July 2017) - Batôt, Guillaume; Fleury, Marc; Nabzar, Lahcen
Abstract: As part of the MiReCOL three-year European project (www.mirecol-co2.eu ) on storage remediation technologies, we studied in the laboratory the capacity of foams to reduce gas flow for CO2-brine systems in rock core sample with common surfactants, as a function of interstitial velocity and gas to water fraction. Two different types of experimental set-up are used. They both allow local measurement of the water saturation for low and high pressure/temperature condition. A small MRI core-flood set-up is used to perform experiments at 35 °C and 10 bars pore pressure, in CO2 non-dense condition. In order to work under reservoir condition, at 40 °C and 130 bars, with dense super-critical CO2 we used a classical core-flood system coupled to an X-ray detection set-up. All experiments were carried out in similar Clashach sandstones with permeability between 220 and 1500 mD, and porosity in the range 10-20%. The gas and the surfactant-brine solution were co-injected at the core inlet face with a gas fraction around 0.7. We vary the interstitial velocity within two decades from about 3 ft/day up to 100 ft/day. The performance of the generated foams was evaluated from the relative foam viscosity, the ratio of the measured pressure drop in the presence of foam to the pressure drop in single phase condition for the same interstitial velocity. Whatever the pressure and permeability/porosity, the relative foam viscosity can be described as a power law vs. the shear rate evaluated from the interstitial velocity, permeability and porosity. The exponent is close to -1 describing the shear-thinning behavior.